Emerging an Innovation through Blended Learning Method in Post Pandemic Era: EFL Learner's Perception - M. Fadhly Farhy Abbas; M. Zaim; Hermawati Syarif; Yetty Zainil (Universitas Muhammadiyah Semarang, 2022)
Blended learning method requires online and offline classroom instruction. In English language class particularly for EFL learners in Indonesia, blended learning become one of the best methods which can be implemented by teacher to assist learners. By having blended learning method, learners are able to do discussion with teacher/lecturer and other students beside face-to-face interaction. This study aims at investigating EFL learner’s perception about blended learning method in language class. This research was a descriptive research. There were 84 learners in university level of English department involved as participants of this study. A questionnaire containing 20 statements about blended learning was used to collect data. The result showed that, EFL learner’s perception about blended learning method was in a positive and good respond. Mostly, EFL learners give respond “agree” and “strongly agree” towards the statement available in the questionnaire. Furthermore, blended learning method can also be implemented by using certain application or platform such as: zoom meeting, google meet, microsoft teams, and others in order to emerge an innovation in a language classroom. In conclusion, blended learning method can create effective and efficient learning.